Digitalisasi Pada Mitra Sampoerna Retail Community (Studi Penggunaan Aplikasi Ayo SRC Di Kecamatan Karas) - Ahmad Fikri Hardiyanto; Tiara Widya Antikasari (Niqosiya: Journal of Economics and Business Research, 2023)
Rapidly developing technology in the MSME sector has caused many companies to start moving in the digital field. One of them is PT Sampoerna through the Sampoerna Retail Community (SRC) partnership program which works with grocery stores in Indonesia to turn a grocery store into a modern store. The digitization program for the SRC partnership itself is implemented through the Ayo SRC application ecosystem which can help shop owners get various kinds of benefits. However, are the SRC partners in the Karas sub-district really running the digitization program? This research is a field research using a qualitative approach to the type of descriptive research. Where data collection using interview techniques. To analyze the data, the writer uses inductive data analysis. Data processing techniques are exposure, sorting and drawing conclusions. Data analysis techniques include data reduction, data presentation and conclusions or verification. To check the validity of the data using triangulation techniques. The informants in this study are shop owners and SRC Coaches in the region. Based on the findings in the field, it shows that digitalization for Sampoerna Retail Community (SRC) partners has been effective. It can be seen from the elements of digital business, namely business people, tools, activities and goals, goals, and some of the benefits that can be obtained, the majority can be fulfilled. Performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC), are considered to be the background for the SRC shop in the Karas sub-district to implement the digitalization program. The digitization program carried out has had an effect on increasing profits and service quality at grocery stores, although it is still not effective because most shops still don't use the Ayo SRC Cashier and Ayo SRC Grocery applications.